Connemara West Centre (Oz, 2000)
Connemara West is a community-owned development organisation which has grown out of a disadvantaged area situated on the western seaboard of County Galway. The project is for a development strategy for the complex, including new buildings and the refurbishment of the former Industrial School to accommodate a furniture college, workshops, furniture restoration unit, student facilities, and administrative headquarters for a wide range of community-led projects.